Efficient Synthesis of Cyclopropanecarboxylic Acid Esters Starting from the Conjugate Addition of Lithium Ester Enolates to 1-Chlorovinyl p-Tolyl Sulfoxides - Kimura, Tsutomu; Hattori, Yoshiaki; Momochi, Hitoshi; Nakaya, Nobuhito; Satoh, Tsuyoshi (Synlett, 2013)
An efficient synthesis of tert-butyl cyclopropanecarboxylates was achieved in three steps using 1-chlorovinyl p-tolyl sulfoxides as key materials. The conjugate addition of lithium ester enolates to the sulfoxides gave tert-butyl 4-chloro-4-(p-tolylsulfinyl)butanoates in high yield. The p-tolylsulfinyl group in the resultant adducts was then removed by the sulfoxide–magnesium exchange reaction with i-PrMgCl at –60 °C. Cyclization of the desulfinylated products, tert-butyl 4-chlorobutanoates, took place in the presence of NaHMDS in a THF–DMPU mixture to afford tert-butyl cyclopropanecarboxylates in good yield. The asymmetric synthesis of both enantiomers of tert-butyl cyclopropanecarboxylate was successfully achieved using optically active (E)- and (Z)-sulfoxides with high enantiomeric excesses.
Keywords: conjugate addition; cyclization; chiral auxiliaries; 1-chlorovinyl p-tolyl sulfoxides; cyclopropanecarboxylates